A thematic analysis of barriers and facilitators to participant engagement in group exposure and response prevention therapy for obsessive–compulsive disorder. (27th October 2022) - Leeuwerik, Tamara; Caradonna, Giorgia; Cavanagh, Kate; Forrester, Elizabeth; Jones, Anna‐Marie; Lea, Laura; Rosten, Claire; Strauss, Clara
Abstract: Exposure and response prevention (ERP) is the gold standard in the treatment of the obsessive–compulsive disorder (OCD). It can be delivered effectively using an individual or group therapy format. Nonetheless, a sizeable proportion of people diagnosed with OCD do not experience OCD symptom remission following ERP. Research suggests that participant engagement with ERP tasks predicts therapy outcomes but there is little consistent evidence across studies on what predicts engagement. A recent meta‐analysis of participant engagement in cognitive‐behavioral therapy for OCD found that group ERP had a comparatively lower dropout rate than individual ERP. Little is known about participant perceptions of ERP to guide an understanding of how the group therapy format may affect participant engagement. This study conducted a qualitative exploration of what helps or hinders participants' engagement in group ERP. It involved thematic analysis of semi‐structured interview data collected at a 6‐month follow‐up from 15 adults with OCD who took part in group ERP. The study identified five main themes that captured participants' perceived facilitators and barriers to engagement in therapy: 'Group processes', 'Understanding how to overcome OCD', 'Personal relevance', 'Personal circumstances', and 'Attitudes towards ERP', which captured dynamically inter‐related barriers and facilitators at the level of the client, therapist, therapy and social environment. Each theme and associated sub‐themes are discussed in turn, followed by a consideration of the study's limitations and implications.